ANALISIS PERMINTAAN KONSUMEN TERHADAP SAYURAN ORGANIK DI PASAR MODERN KOTA PEKANBARU - Junipranto Silitonga; Salman Salman (DINAMIKA PERTANIAN, 2014)
In modern community, the healthy llife pattern has become one of quality standards. The healthy life pattern can be begun to consumer organic vegetables. The organic vegetable is produced by utilizing organic matters without using synthetic chemicals. The purpose of research was to examine factors affecting consumer demand on organic vegetables and to analyze the relationship between social economic factors (age, education level, family member and consumer income) and purchasing decision of organic vegetables. The survey sites was chosen in Pekanbaru City, namely Mall SKA, Mall Ciputra, and Fruit Market and conducted on December 2014. The results showed that factors affecting significantly on consumer demand of organic vegetables was price, while price of inorganics vegetable, income, family member, and dummy had not significantly influence on consumer demand of organic vegetable. Factors, like age, education, income, and family member, had no relationship with consumer decision in consuming organic vegetables.